1987
DOI: 10.1111/j.1365-3180.1987.tb00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the uptake, movement and metabolism of fluroxypyr in Stellaria media and Viola arvensis

Abstract: Summary The uptake, movement and metabolism of fluroxypyr* is compared in two contrasting weed species, Stellaria media (susceptible) and Viola arvensis (moderately resistant). Similar rates of uptake occurred in both species, with a rapid cuticular uptake of 50% of that applied within 4 h. Total uptake by the underlying leaf tissue reached 66.6% and 70.8% in S. media and V. arvensis after 7 days. In translocation studies, in which 14C‐fluroxypyr was applied to previously sprayed plants, 5.1% of applied 14C‐ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
2
8
1
Order By: Relevance
“…Fluroxypyr ϩ 2,4-D was the only herbicide combination that provided control both when precipitation was less than 15 cm during the growing season (2002) and when precipitation was 19 to 32 cm during the growing season (2003). This finding contradicts previous reports, which classify field violet as moderately tolerant of fluroxypyr and suggest that efficacy of fluroxypyr is lower under drought conditions (Bouma et al 1996;Hannan-Jones 1998;Sanders and Pallett 1987b). However, in this study it may be that this herbicide compounded injury due to drought stress by stimulating auxin-regulated growth during a period when most plants had become quiescent.…”
Section: Implications Of Results Control Of Field Violet Withcontrasting
confidence: 99%
See 1 more Smart Citation
“…Fluroxypyr ϩ 2,4-D was the only herbicide combination that provided control both when precipitation was less than 15 cm during the growing season (2002) and when precipitation was 19 to 32 cm during the growing season (2003). This finding contradicts previous reports, which classify field violet as moderately tolerant of fluroxypyr and suggest that efficacy of fluroxypyr is lower under drought conditions (Bouma et al 1996;Hannan-Jones 1998;Sanders and Pallett 1987b). However, in this study it may be that this herbicide compounded injury due to drought stress by stimulating auxin-regulated growth during a period when most plants had become quiescent.…”
Section: Implications Of Results Control Of Field Violet Withcontrasting
confidence: 99%
“…The weed was not controlled by dicamba at 0.4 kg ai/ha (Doohan and Monaco 1992) and was classified as tolerant to 2,4-D and mecoprop (Ontario Weed Committee 1988). Fluroxypyr was found to be ineffective because the active form of the herbicide is not readily translocated and is rapidly conjugated to nonphytotoxic polar metabolites (Sanders and Pallett 1987b). Bentazon alone and bentazon ϩ bromoxynil ϩ clopyralid (0.95 ϩ 0.25 ϩ 0.05 kg ai/ha) had no effect on field violet (Froment and Turley 1998).…”
Section: Introductionmentioning
confidence: 99%
“…media cell division appeared to be initiated exterior to the phloem, although the immature state of the stem made exact identification of individual cells difficult. This proliferation of meristematic activity is in agreement with previous studies of fluroxypyr activity which have shown that greater than 60% of the penetrated fluroxypyr was translocated to the stem of S. media within 7 days of treatment (Sanders & Pallett, 1987).…”
Section: Discussionsupporting
confidence: 92%
“…Taylor et al (23) noted a broadleaf herbicide, fluroxypyr (Spotlight), did not antagonize efficacy of aryloxyphenoxypropionic herbicides, such as fenoxaprop. Fluroxypyr is a pyridinoxy acid herbicide, recently registered for use in turf, with activity on annual and perennial broadleaf weeds (2,20,21).…”
Section: Introductionmentioning
confidence: 99%